Minimally invasive video‐assisted thyroidectomy in Asian patients: experience from Singapore. Issue 9 (31st July 2020) - Singaporewalla, Reyaz M.; Rao, Anil D.
Abstract: Background: Minimally invasive video‐assisted thyroidectomy (MIVAT) although well established in Europe has not yet gained widespread acceptance in Asia. We describe our learning experience in the first reported series of 105 cases from Singapore. Methods: A retrospective analysis of outcomes in 105 patients who underwent MIVAT from April 2011 to 2018 was performed. The inclusion criteria were – symptomatic benign thyroid pathologies and follicular lesions or neoplasms needing a hemi‐thyroidectomy. A thyroid lobe volume less than 35 mL was used as cut‐off. Patients underwent surgeon‐performed thyroid ultrasound with biopsy of solid nodules. All cases were operated by one surgeon using standard Miccoli technique with energy device used in all cases. Results: From a total of 424 patients with nodular goitres undergoing thyroidectomy, 105 (24%) symptomatic eligible patients underwent the MIVAT procedure (M:F – 23:82). The mean incision lengths at start and completion were 1.7 cm (range 1.5–2 cm) and 2.4 cm (range 2–2.7 cm), respectively. Mean operating time was 97 min (range 59–160 min). There were four conversions (3.8%) in the first 25 cases and four patients (3.8%) experienced transient hoarseness with full recovery. Visual analogue pain scores at 6 and 24 h post‐operatively were 2.7 and 1.1, respectively. Scar satisfaction was reported as excellent (75%), satisfactory (23%) and poor (2%). Conclusion: Although technically more demanding, MIVAT is a safe and useful operation in a thyroid surgeon's armamentarium. The limitation of goitre size, however, allows only a small percentage of symptomatic patients to undergo this procedure. Abstract : This is the first large series of patients undergoing MIVAT from Singapore. We present our learning experience, results and cosmetic satisfaction in Asian patients.